PTU-016 Quality of ercp services in district hospitals in the northern region – a 3-month audit. (23rd September 2015) - Nylander, D; Chatterjee, S; MacDougall, L; Greenaway, J; Dwarakanath, D; MacDonald, C; Barton, R; Gregory, W; Rees, C
Abstract : Introduction: ERCP is an important tool in the diagnosis and treatment of pancreaticobiliary disease. It is associated with complication rates between 4-30%. We assessed ERCP practice in the Northern Region (NR) against the results found in the BSG audit (BSGA).1 Methods: Data were collected prospectively from all ERCPs performed in DGHs in the NR over a 3-month period, followed by a notes review >30 days later to look for complications. These hospitals provided ERCP services for their local population only. A questionnaire about ERCP service in each trust and giving total number of procedures over 12 months was completed by a senior endoscopist. Results: Data were obtained from eight acute trusts in which a total of 23 ERCP endoscopists performed procedures. Over 12 months these units undertook a median 280 procedures (range 150–372). During the period of the audit there were 467 procedures performed. 367 of these were first procedure the patient had encountered. 84% were ASA grade I or II, 14% grade III and 2% grade IV. All patients had radiology imaging before their first ERCP. All procedures were performed to achieve biliary therapy.First procedure details are shown in Abstract 016 (BSGA figures in brackets). All procedures performed using conscious sedation. 5.5% of patients had Midazolam dose >5 mg (33% BSGA), and in all these cases this was combined with an opioid. Reversal agent was not used in any of these but in only 1 other case in entire series (7.6% BSGA). 30-day complication was reported in 25 cases (included pancreatitis -6; significant bleed-4; cholangitis-3, hepatic abcess-1). Includes 9 deaths; 1 definitely, and 2 possibly ERCP related (0.4% BSGA). Conclusion: The Northern Region provides a high standard of ERCP performance exceeding results seen in BSGA. Complication rates were low. More information on comparative data from individual endoscopists possibly by greater use of ERCP quality network (Peter Cotton) will be used to encourage further improvement in standards. Abstract submitted on behalf of Northern Region Endoscopy Group.